The growth effect of external debt and FDI in sub-Saharan Africa: The role of institutional quality - Mark, Robert Kinuthia- (Strathmore University, 2021)
Much of the literature on the relationship between external debt, FDI and economic growth focus on the direct effect external debt and FDI has on economic growth. It is difficult to find research addressing the role of institutions in the relationship between the three variables. This study aims to investigate the effect institutional quality has on the relationship between external debt and FDI on economic growth. To achieve this objective, the fixed effects model is estimated with data from 6 Sub-Saharan African countries over the years 2000 to 2018. The empirical results find that both the interaction terms between external debt and corruption, and FDI and corruption to be positive and statistically significant. This confirms the institutional quality of an economy play a role in the effect external debt and FDI have on economic growth. It is determined that when countries have stronger institutions, the effect of external debt and FDI on economic growth is enhanced.
Submitted in partial fulfilment of the requirements for the Degree of Bachelor of Business Science in Financial Economics at Strathmore University